2018
DOI: 10.1177/1073274818806900
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Lung Cancer Screening Beliefs and Practice Patterns for Community Providers Compared to Academic Providers

Abstract: Despite guidelines recommending annual low-dose computed tomography (LDCT) screening for lung cancer, uptake remains low due to the perceived complexity of initiating and maintaining a clinical program—problems that likely magnify in underserved populations. We conducted a survey of community providers at Federally Qualified Health Centers (FQHCs) in Santa Clara County, California, to evaluate provider-related factors that affect adherence. We then compared these findings to academic providers’ (APs) LDCT scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…Similar to other cancer screening contexts, we found that clinician recommendations played a substantial role in patient ratings of anticipated screening [eg, ], highlighting the importance of clinician‐patient communication and training with regard to LCS and shared decision making. However, some previous studies of primary care clinicians have demonstrated suboptimal knowledge, attitudes, and practices with regarding to LCS. For example, only 22% to 31% of primary care providers knew the correct LCS eligibility criteria, which led to inappropriate LCS referrals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to other cancer screening contexts, we found that clinician recommendations played a substantial role in patient ratings of anticipated screening [eg, ], highlighting the importance of clinician‐patient communication and training with regard to LCS and shared decision making. However, some previous studies of primary care clinicians have demonstrated suboptimal knowledge, attitudes, and practices with regarding to LCS. For example, only 22% to 31% of primary care providers knew the correct LCS eligibility criteria, which led to inappropriate LCS referrals.…”
Section: Discussionmentioning
confidence: 95%
“…However, some previous studies of primary care clinicians have demonstrated suboptimal knowledge, attitudes, and practices with regarding to LCS. For example, only 22% to 31% of primary care providers knew the correct LCS eligibility criteria, which led to inappropriate LCS referrals. Thus, our research highlights the need for up‐to‐date knowledge about LCS among primary care providers.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, previous studies have demonstrated that physicians who are aware of the guidelines are more likely to initiate discussions of lung cancer screening with their patients (45) and order LDCT screening tests (45,46). However, since the USPSTF's endorsement of LDCT screening, multiple institutional reports have shown that primary care physicians in underserved areas have a relatively limited understanding of the guidelines and their supporting evidence (47)(48)(49)(50)(51)(52). While the exact reasons for this uncertainty are not well known, discordance between NCCN and USPSTF indications for screening, lack of familiarity of the survival benefit associated with LDCT screening, and concerns regarding false positive rates and excess harms to the patient may all play a role (49)(50)(51)53).…”
Section: Improving Awareness Of Ldct Screening Among Healthcare Providersmentioning
confidence: 99%
“…However, since the USPSTF's endorsement of LDCT screening, multiple institutional reports have shown that primary care physicians in underserved areas have a relatively limited understanding of the guidelines and their supporting evidence (47)(48)(49)(50)(51)(52). While the exact reasons for this uncertainty are not well known, discordance between NCCN and USPSTF indications for screening, lack of familiarity of the survival benefit associated with LDCT screening, and concerns regarding false positive rates and excess harms to the patient may all play a role (49)(50)(51)53). Efforts to familiarize healthcare providers with these topics through the distribution of educational materials and group based learning methods have been shown to be feasible at individual centers (54).…”
Section: Improving Awareness Of Ldct Screening Among Healthcare Providersmentioning
confidence: 99%
“…It was estimated that 6.8 million smokers were eligible for LDCT screening, while only 3.9% of eligible Americans reported receiving screening for lung cancer with LDCT in 2015 [8]. Reasons for low uptake of screening may include gaps in patients' knowledge about the LDCT screening, lack of access to health care [9][10][11], and physicians' knowledge and perception regarding the screening recommendation and patient cost [11][12][13][14][15][16][17][18]. For most adult patients in the U.S., primary care providers (PCPs) play a critical role in offering preventive healthcare and screening; therefore, an understanding of PCPs' utilization and perceptions on lung cancer screening guidelines is necessary to improve appropriate assessment and referrals for specialty care services, as well as overall implementation of the screening procedure.…”
Section: Objectivementioning
confidence: 99%